American port.. T.B. The ethnic potpourri - Saunders, M., Lewinski, M. (Arlington MetaTech Corporation)
This book describes the main processes in the USA, connected with immigration, amecarization and how to become a real member of the USA, what are the main laws people must obey. Its teachers book so the information is not very detailed but very useful and interesting.
Keywords: English Practice